Deskripsi Hasil Belajar Geografi Berdasarkan Gaya Belajar Siswa Kelas XI IPS SMA Negeri 1 Wangi-Wangi Kabupaten Wakatobi - Jamal; Sitti Kasmiati; Andrias (Jurnal Penelitian Pendidikan Geografi, 2023)
Education in Indonesia faces formidable challenges. The demand to develop human resources through education absolutely must be carried out with the hope of creating superior human beings, one of which is by understanding student learning styles. The purpose of this study is to find out the description of learning outcomes in Geography based on the learning styles of class XI students at SMA Negeri 1 Wangi-Wangi, Wakatobi Regency. This type of research applied is descriptive quantitative. The population of this study was 93 respondents taken from class XI IPS. The results showed that there were 46 students with a visual learning style and 47 students with an auditory learning style. The description of student learning outcomes shows that the visual learning style has a higher average value (dominant) than students with an auditory learning style.